2021
DOI: 10.3389/fpsyt.2021.777251
|View full text |Cite
|
Sign up to set email alerts
|

Post-secondary Student Mental Health During COVID-19: A Meta-Analysis

Abstract: The COVID-19 pandemic has posed notable challenges to post-secondary students, causing concern for their psychological well-being. In the face of school closures, academic disruptions, and constraints on social gatherings, it is crucial to understand the extent to which mental health among post-secondary students has been impacted in order to inform support implementation for this population. The present meta-analysis examines the global prevalence of clinically significant depression and anxiety among post-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 240 publications
3
33
2
3
Order By: Relevance
“…Our results are in line with other studies which found elevated levels of depression and anxiety among university students (3)(4)(5)21). First of all, students are vulnerable because of high levels of financial difficulties as well social isolation, which increased during the course of the epidemic (21,22).…”
Section: Mental Health Of Studentssupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are in line with other studies which found elevated levels of depression and anxiety among university students (3)(4)(5)21). First of all, students are vulnerable because of high levels of financial difficulties as well social isolation, which increased during the course of the epidemic (21,22).…”
Section: Mental Health Of Studentssupporting
confidence: 93%
“…In the general population, factors associated with a deterioration in mental health include female sex, age under 35 years, loneliness and low income (2). In addition, several studies have found that university students experienced especially large increases in the prevalence of depression and anxiety disorders, with approximately a third suffering from either condition (3)(4)(5). However, most of these studies were conducted in China (3)(4)(5) where the spread of COVID-19 was limited after 2019 and accompanied by strict preventive measures, or in the United States (3) where to the contrary, the toll of the COVID-19 epidemic has been high and distance teaching was implemented for extended periods of time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, differences in prevalence have been found in connection with geographical area, financial situation, and living arrangements ( 24 ). Inconsistent results have been found regarding the sex/gender variable ( 27 ). In addition, the month of data collection and geographical region were determined to be significant moderators of the prevalence ( 27 ).…”
Section: Introductionmentioning
confidence: 91%
“…Inconsistent results have been found regarding the sex/gender variable ( 27 ). In addition, the month of data collection and geographical region were determined to be significant moderators of the prevalence ( 27 ). Perceived social support, one of the most frequently studied variables, exhibits an inverse association with depression among students (e.g., ( 29 )).…”
Section: Introductionmentioning
confidence: 91%